Examining Workplace Bullying and Insomnia on Employees with the Mediating Role of Emotional Exhaustion and Moderating Effect of Employee Resilience - Mahmood, Kashif; farid, Mehar; Rashid, Munazza (Journal of Applied Research and Multidisciplinary Studies, 2023)
The current study aimed to investigate the impact of workplace bullying and insomnia on employees and tested the mediation of emotional exhaustion and moderation of employee resilience in the organisation. In the current study, emotional exhaustion was taken as a mediator and employee resilience moderated the workplace bullying and insomnia. This study was conducted to fill the gap pointed out in the literature. The population selected for data collection comprised NLC industries. The respondents selected for data collection included managers and employees. The current study used convenient samping technique to gather the data. The software applied in this study was PROCESS MACRO model 7 which tests the direct and indirect effects of moderation and mediation in this conceptual framework. Based on the convenience sampling technique, the respondents (n = 464) worked across different areas in Punjab. To test the hypotheses, the current study investigated how workplace bullying affected the working behaviour of employees. Social exchange theory was applied to support this framework. As emotional exhaustion mediated between workplace bullying and insomnia of the employees, many hypotheses have been accepted from the suggested list by the statistical analysis. The empirical evidence shows that workplace bullying significantly triggers insomnia among employees and employee resilience is affected positively, hence the negative outcome is reduced. The current study provided guidelines for managers to overcome the employees’ negative behaviour at workplace which would ultimately enhance the productivity and performance of the organization.